Доповнюємо сторінки родоводу П. О. Куліша - Міллер, Н.В. (Сіверщина в історії України, 2025)
Дослідження доповнює сторінки родоводу визначного українського культурного діяча – письменника Пантелеймона Олександровича Куліша. У статті наведена інформація з документів, які раніше залишалися поза увагою дослідників, що висвітлюють походження воронізького роду Кулішів. До обігу уводиться родовідне дерево Кулішів, складене батьком письменника – Олександром Андрійовичем Кулішем. За результатами опрацювання присяг та ревізій Воронізької сотні подаються нові відомості про Пантелеймонового прадіда, сотенного воронізького отамана Івана Куліша, уводяться нові імена, які належали до членів родини, простежується їхній життєвий шлях. Уперше оприлюднено витяги зі сповідних розписів церков містечка Вороніж за 1739 р., 1756 р. та метричної книги воронізької Трьохсвятительської церкви за 1802–1811-і роки, що суттєво доповнить знання про воронізьку родину Кулішів. The research complements the genealogy pages of the prominent Ukrainian cultural figure and writer Panteleimon Oleksandrovych Kulish, born in the northern town of Voronezh. The article provides information from previously unknown archival documents that shed light on the origins of the Kulish family of Voronezh. The genealogy tree of the Kulish family, compiled by the writer’s father, Oleksandr Andriiovych Kulish, is introduced. Based on the results of the processing of oaths and revisions of the Voronezh hundred, new information about Panteleimon’s great-grandfather, the centurion Voronezh ataman Ivan Kulish, is presented, new names belonging to family members are introduced, and their life paths are traced. Extracts from the confessional records of the town of Voronezh for 1739, 1756, and the metric book of the Voronezh Trinity Church for 1802-1811 are published, significantly supplementing knowledge about the Voronezh Kulish family. For the first time in this study, the writer’s genealogy is derived from previously unlit archival documents, new family members are identified, a graphical genealogy tree is presented, and specific birth dates of individual family members, including Panteleimon’s father – Oleksandr Andriiovych, are named.